Integrating Islamic Environmental Ethics into Legal Frameworks: The Role of Hima, Primum Remedium, and Strict Liability in Protecting Mining-Affected Communities - Hakim, Sofyan; Jalaluddin; Sukarni; Abas, Mujiburohman Abul; Jamil, Abdul; Hafizi, Muhammad Riza (Jurnal Studi Agama dan Masyarakat, 2025)
The increasing number of exploitations in mining is a threat, which has a serious impact on environmental damage and causes social, economic, and ecological losses. Meanwhile, the legal mechanism of environmental ethics has not been fully effective in terms of comprehensive protection in prevention or recovery. The study aimed to analyze the integration of Islamic environmental ethics principles into the legal framework of the role of hima conservation, primum remedium, and strict liability in strengthening environmental law. The method used normative juridical with a conceptual approach, case approach, and sources of Islamic law. The findings show that the hima conservation area is a place for traditional heritage conservation that maintains harmony among culture, humans, and the environment following the principle of maqasid syari’ah. Meanwhile, the limitation of industrial exploitation under the principle of primum remedium in positive law emphasizes the use of criminal law as a preventive measure and strict liability or absolute responsibility without any proof of fault. These three principles, if applied systematically into the framework of modern environmental law reform that integrates Islamic ethical principles into national environmental laws, will strengthen ecological justice and protection. It is supported by moral, cultural, and spiritual responsibility to protect the environment and build a sustainable legal system.